CHALLENGE FOR THE ISLAMIC STUDIES SENIOR HIGH SCHOOL TEACHER IN IMPLEMENTING THE 2013 CURRIC ULUM IN SMAN 1 SALATIGA - Nur Laili Noviani (Analisa: Journal of Social Science and Religion, 2016)
As one of the main subjects in senior high school education, Islamic studies play an important role, even though it is not included in the final exam for third-grade students. Similar to the other teachers, the Islamic studies teacher also has challenges on implementing Islamic education based on the 2013 curriculum. Employing descriptive qualitative method, this research focused on describing what challenges that Islamic studies teachers faced during the implementation of the 2013 curriculum. Data was collected from interview and observation. Data reduction was used as data being analyzed. This research was completed in 2015 and it took place in SMAN 1 Salatiga where the 2013 curriculum has been implemented since 2013/2014 and the implementation was one of the pilot projects of the school. This research finds out that individual differences and the complexity of evaluation standard are the main challenges for the teachers. Individual differences do not only apply to students but also teachers. The complexity of evaluation standard is also significant to challenge the teachers on implementing Islamic education based on a whole 2013 curriculum.